Working capital management and firm profitability during a period of financial crisis: empirical study in emerging country of Vietnam - VU, Manh Chien; Phan, Thanh Tu (Advances in Social Sciences Research Journal, 2016)
This paper analyzes the relationship between working capital management and profitability from operations of 121 firms listed on the two stock exchanges, i.e. Hanoi Stock Exchange (HNX) and Ho Chi Minh Stock Exchange (HOSE) in the period 2008-2012. The research result has indicated that Receivables Collection Period (RCP), Ratio of debt to total assets (LEV), Current Ratio (CR) has negative correlation; whereas Growth of Sales (GOS) and Size of Companies (SIZE) have positive with the firm’s return on equity (ROE). The research findings of researches provide experimental evidence to confirm the important role of working capital management that has direct effect on profitability of firms. Particularly in financial crisis, the managers should accord a particular attention on solutions concerning Receivables Collection Period; by justifying the Leverage and Current Ratio at reasonable level; by enhancing measures for increasing the growth of sale in order to stabilize the firm